Faktor-Faktor yang Mempengaruhi Keberhasilan Implementasi Sistem Informasi Enterprise di Perusahaan - Nugraha, Cecep; Diman, Yosa Eka (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the factors influencing the successful implementation of Enterprise Information Systems (EIS) in companies, particularly in the context of the increasing need for data integration and operational effectiveness due to advances in information technology. Although EIS can offer various strategic benefits such as increased efficiency, information accuracy, and interdepartmental coordination, its implementation often encounters obstacles due to technical complexity and organizational readiness. Using a descriptive qualitative approach based on literature review, this study identifies key elements of successful implementation, including organizational readiness, top management support, human resource competency, system alignment with business processes, and an adaptive organizational culture. The results indicate that implementation success is determined not only by system quality but also by the organization's ability to manage change, overcome user resistance, and ensure the system aligns with the company's strategic needs. These findings confirm that EIS implementation requires a holistic approach that integrates human factors, business processes, and technology for optimal system performance and long-term value for the company.